Juridical Review of Criminal Acts of Blatantly and With Joint Force Carrying Out Violence Against People and Property (Article 170 of the Criminal Code) - Viernanda Prahma Radhyvkha; Muchammad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
The Penal Code is a law that regulates punishment, especially actions that are felt to cause harm to others such as theft, violence, murder, fraud and various other criminal acts. The Penal Code is also equipped with sanctions that will be given to someone who commits violations, both in the form of fines, imprisonment, to the death penalty. The Penal Code has also been amended several times in order to provide legal certainty for all levels of society. Article 170 of the Indonesian Civil Code is one of the articles that focuses on legal protection of people and goods from criminal acts. This article leads to the protection of public order from irresponsible people. Islam as a religion that has perfection and complete rules is felt to also have various provisions regarding this, because Islam is a religion that brings mercy to all nature. This study uses Juridical‐Normative research methods with the aim of providing a broad description of article 170 of the Indonesian Civil Code and providing an Islamic picture of things like this.